2020
DOI: 10.18632/aging.103239
|View full text |Cite
|
Sign up to set email alerts
|

UBE2T promotes glioblastoma invasion and migration via stabilizing GRP78 and regulating EMT

Abstract: Glioblastoma (GBM) generally has a dismal prognosis, and it is associated with a poor quality of life as the disease progresses. However, the development of effective therapies for GBM has been deficient. Ubiquitin-conjugating enzyme E2T (UBE2T) is a member of the E2 family in the ubiquitin-proteasome pathway and a vital regulator of tumour progression, but its role in GBM is unclear. In this study, we aimed to clarify the role of UBE2T in GBM. Bioinformatics analysis identified UBE2T as an independent risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Besides HMMR, the other four hub genes (UBE2T, PTTG1, GINS2 and TYMS) have been shown to play a role in HCC. UBE2T, a member of the E2 family, is demonstrated to be a vital regulator of tumor progression in several cancers, such as lung cancer [63], glioblastoma [64], and HCC [65]. PTTG1 has been reported to be associated with poor prognosis in multiple myeloma [66], prostate cancer [67] and HCC [68].…”
Section: Discussionmentioning
confidence: 99%
“…Besides HMMR, the other four hub genes (UBE2T, PTTG1, GINS2 and TYMS) have been shown to play a role in HCC. UBE2T, a member of the E2 family, is demonstrated to be a vital regulator of tumor progression in several cancers, such as lung cancer [63], glioblastoma [64], and HCC [65]. PTTG1 has been reported to be associated with poor prognosis in multiple myeloma [66], prostate cancer [67] and HCC [68].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing UBE2C causes pancreatic ductal adenocarcinoma cells to block in the G1/S phase, and reduces the levels of EMT markers (VIM, E-cadherin) [ 182 ]. E2s that regulate EMT also include UBE2O, UBE2V1, and UBE2T [ 183 ]. Flavopiridol can significantly inhibit the activity of CDKs (1/2/4/6/7) by interacting with the ATP binding pocket on the kinase, thereby causing G1/G2/M phase block.…”
Section: Biological Processes Involving E2smentioning
confidence: 99%
“…In addition, knockdown of UBE2T could inhibit cell proliferation and invasion via regulating the PI3K/Akt signaling pathway in osteosarcoma (10). UBE2T have reported to accelerate glioblastoma invasion via regulating GRP78 (11). Yin et al found that UBE2T promotes epithelial-mesenchymal transition through mediating FOXO1 degradation in non-small cell lung cancer (12).…”
Section: Introductionmentioning
confidence: 99%